Composites of Li-Al-B-Si-O glass and β-Al2O3 for LTCC-silicon heterogeneous integration applications. (November 2018) - Chen, Guanyu; Liu, Zhifu; Ma, Mingsheng; Zhang, Faqiang; Li, Yongxiang; Wen, Zhaoyin; Wu, Xiangwei
Abstract: Composites of Li-Al-B-Si-O (LABS) glass and β-Al2 O3 have been synthesized for low-temperature co-fired ceramics (LTCC) technology application. The main phase of sintered composites is Li2 Al2 Si3 O10 and β-Al2 O3 phase appears only when its content is higher than 35 wt%. The DC conductivities of sintered composites are all above 1 × 10 −8 S/cm at the temperature of 473 K. The activation energies of alkali ions of different composites are all between the conductivity measured perpendicular and parallel to the c-axis of Eucryptite, which proves the ionic conductance of composites is associated with the main phase of Li2 Al2 Si3 O10 . The CTE of the composites increased with the increase of β-Al2 O3 . The CTE of 68 wt% LABS glass-32 wt% β-Al2 O3 is 3.15 ppm/°C (25–300 °C), which matches that of silicon (3.2 ppm/°C, 25–300 °C) well. The results indicate that the composites of Li-Al-B-Si-O glass and β-Al2 O3 can be a promising material for LTCC-silicon heterogeneous integration with anodic bonding technology.